Histological and Physiological Effects of Treatment of Rudbeckia hirta with Gamma Radiation - Szilvia Kisvarga; Dóra Hamar-Farkas; Katalin Horotán; Ádám Solti; Edina Simon; Máté Ördögh; András Neményi; Gábor Boronkay; László Orlóci (Plants, 2023)
The breeding of resistant, high-yield, decorative ornamental plant varieties may be impacted by climate change in the future. The use of radiation induces mutations in plants, thereby increasing the genetic variability of plant species. Rudbeckia hirta has long been a very popular species in urban green space management. The goal is to examine whether gamma mutation breeding can be applied to the breeding stock. Specifically, differences were measured between the M1 and M2 generations, as well as the effect of different radiation doses belonging to the same generation. Morphological measurements showed that gamma radiation has an effect on the measured parameters in several cases (larger crop size, faster development, larger number of trichomes). Physiological measurements (examination of chlorophyll and carotenoid content, POD activity, and APTI) also showed a beneficial effect of radiation, especially at higher doses (30 Gy), for both tested generations. The treatment was also effective in the case of 45 Gy, but this radiation dose resulted in lower physiological data. The measurements show that gamma radiation has an effect on the Rudbeckia hirta strain and may play a role in breeding in the future.